In vitro Inhibition of Border Disease Virus Replication With Lentivirus-Mediated shRNAs - Arani, Mohammad Javad Hajihasani; Mokhtari, Azam; Saffar, Behnaz; Asadi Samani, Leila (Frontiers in Veterinary Science, 2021)
Background: Border disease is believed to be one of the most important diseases in the animal husbandry industry, which has not yet been eradicated in Iran. The development of approaches based on the application of interfering RNA (RNAi) for antiviral therapy has attracted a great deal of attention over the recent years. The present research was conducted to design, construct, and apply shRNA against the NS3 gene of BDV to evaluate the prevention of BDV proliferation in the cell culture system. For this purpose, the suitable oligonucleotide sequence of NS3 gene coding was selected utilizing BDV- X818 strain. Afterwards, using shRNA design software, shRNA molecules were designed and synthesized. These shRNAs were cloned into the desired vectors and were finally transfected in HEK293T cells employing the third generation of lentiviral packaging system. Subsequently, these shRNA expressing lentiviruses were transduced to the MDBK cell line to challenge to border virus. In order to evaluate the efficacy of shRNAs, the viral infectious titer and RNA copy number were calculated with TCID50 and Real-time RT-PCR tests, respectively. Results: The results revealed that shRNAs 1, 2, and 3 decreased viral RNA by more than 90% compared to the control groups. BDV titer noticeably decreased after the challenge with shRNAs 1, 2, and 3 from approximately 88% up to 99% in comparison with the control groups. Conclusions: Overall, it could be concluded that RNAi may be considered as a strong treatment proposal against viruses, such as BDV.